Analisis Perhitungan dan Pelaporan Pajak Pertambahan Nilai pada Perum Perumnas Proyek Sukaramai - Rebecca Oktavia; Susilawati; Sondang Beatrix Siahaan (Universitas Palangka Raya, 2023)
This research aims to find out how the calculation and reporting of Pajak Pertambahan Nilai at Perum Perumnas Proyek Sukaramai and to find out whether the calculation and reporting of Pajak Pertambahan Nilai is in accordance with the Act Number 42 of 2009 concerning Pajak Pertambahan Nilai. The techniques of data collection is by doing technical documentation and processed using descriptive analysis method. The research period is August to December 2021. The results show that the calculation and reporting of Pajak Pertambahan Nilai at Perum Perumnas Proyek Sukaramai is in accordance with the Act Number 42 of 2009, although there was an error in the calculation in August 2021.